Necesidad de insertar en el código orgánico de la niñez y adolescencia la figura legal de tenencia compartida de los menores de edad fruto del matrimonio - André Córdova, Yoselyn Yokasta (2017)
The rule contained in article 69, paragraph 5 of the Constitution of the Republic of Ecuador provides that the State protects parents and to parents in the exercise of their duties. It will promote paternal and maternal responsibility and monitor the performance of the duties and reciprocal rights between parents and children. However within the Civil Code is not regulated the co-responsibility of parents in case of divorce, single post recognized the custody parent, when the standard Constitution recognizes the joint custody as the most suitable mechanism that causes less impact on children in cases of separation from their parents. Parties more difficult and painful for a mother or a father who raises only to their children is the subject of custody and visits. Parents have to come to an agreement as to the responsibilities of each, the custody and visitation rights until the child is 18 years, but if they are not in agreement, the judge has to decide. One in four children whose parents are in separation process with conflicts by their custody suffers from the syndrome, Parental alienation or SAP, a State caused by the manipulation of children by a parent (normally or who have custody) against the other parent and causes, in greater or lesser degree , the rejection of the children to the latter. In these circumstances arises the shared custody is the legal situation whereby, in the event of marital separation or divorce, both parents have legal custody of their minor children, on equal conditions and rights over them. In this regard article 69, paragraph 5 of the Constitution of the Republic of Ecuador establishes that the State protects parents and to parents in the exercise of their duties. It will promote paternal and maternal responsibility, will monitor the performance of the duties and reciprocal rights between parents and children, therefore establishes joint custody, from there the need to insert in the organic code of childhood and adolescence the legal figure of shared ownership of children resulting from the marriage.